Personnel marketing as a guarantee of recruitment improvement (Journal of Economic Research & Business Administration, 2016)
The present paper develops the idea of personnel marketing application with the purpose of meeting recruitment needs. Personnel marketing-becomes more popular among companies as it successfully complements to their development solving a range of relevant issues. One of those issues is satisfying recruitment needs of short and long-term character. The paper also covers the challenges of companies applying personnel marketing in their business activities and defines an HR brand andan employer brand. The distinctive features of the employer practicing personnel marketing are specified by the authors. Additionally the key functions of personnel marketing are described. The main objective of the paper is demonstration of the advantages of companies practicing personnel marketing in comparison with their competitors not applying it. The specificity of recruitment steps implementation by the mentioned companies is analyzed in detail. Finally, the paper concluded positive influence of personnel marketing on human resource management by satisfying short-term recruitment needs and securing long-term recruitment tasks.
Keywords: personnel marketing (PM); recruitment; HR-brand; employer brand; steps of personnelrecruitment; recruitment needs.